Modulating O2 reactivity in a fungal flavoenzyme: involvement of aryl-alcohol oxidase Phe-501 contiguous to catalytic histidine - Hernández-Ortega, Aitor; Lucas, Fátima; Ferreira, Patricia; Medina, Milagros; Guallar, Victor; Martínez, Angel T (The Journal of biological chemistry, 2011)
Aryl-alcohol oxidase (AAO) is a flavoenzyme responsible for activation of O(2) to H(2)O(2) in fungal degradation of lignin. The AAO crystal structure shows a buried active site connected to the solvent by a hydrophobic funnel-shaped channel, with Phe-501 and two other aromatic residues forming a narrow bottleneck that prevents the direct access of alcohol substrates. However, ligand diffusion simulations show O(2) access to the active site following this channel. Site-directed mutagenesis of Phe-501 yielded a F501A variant with strongly reduced O(2) reactivity. However, a variant with increased reactivity, as shown by kinetic constants and steady-state oxidation degree, was obtained by substitution of Phe-501 with tryptophan. The high oxygen catalytic efficiency of F501W, ∼2-fold that of native AAO and ∼120-fold that of F501A, seems related to a higher O(2) availability because the turnover number was slightly decreased with respect to the native enzyme. Free diffusion simulations of O(2) inside the active-site cavity of AAO (and several in silico Phe-501 variants) yielded >60% O(2) population at 3-4 Å from flavin C4a in F501W compared with 44% in AAO and only 14% in F501A. Paradoxically, the O(2) reactivity of AAO decreased when the access channel was enlarged and increased when it was constricted by introducing a tryptophan residue. This is because the side chain of Phe-501, contiguous to the catalytic histidine (His-502 in AAO), helps to position O(2) at an adequate distance from flavin C4a (and His-502 Nε). Phe-501 substitution with a bulkier tryptophan residue resulted in an increase in the O(2) reactivity of this flavoenzyme.